2021
DOI: 10.1111/jpn.13550
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, tissue precipitation, metallothionein and cytokine transcript expression and economics in response to different dietary zinc sources in growing rabbits

Abstract: Multidrug resistance bacteria are considered a public health threat.Several previous studies revealed the emergence of multidrugresistant bacterial pathogens from different origins that increase the need for dietary supplements to improve animal immunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…In the present study, only ZnO reduced serum IL-1β level of 28-day-old calves compared with the CON group. This is similar to a previous study in growing rabbits [11], in which supplementary 50 mg/d ZnPro did not affect serum IL-1β concentration. IL-10 has protective effects on the intestinal mucosal barrier [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, only ZnO reduced serum IL-1β level of 28-day-old calves compared with the CON group. This is similar to a previous study in growing rabbits [11], in which supplementary 50 mg/d ZnPro did not affect serum IL-1β concentration. IL-10 has protective effects on the intestinal mucosal barrier [29].…”
Section: Discussionsupporting
confidence: 92%
“…Zinc can be transferred into the circulatory system through MT during intestinal absorption, so MT can regulate Zn balance and metabolism in the body [11,37]. In addition, an MT molecule can combine with seven Zn ions to scavenge ROS in liver and bone marrow cells; its scavenging ability of •OH is 300-fold greater than GSH-Px [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is an essential trace mineral for humans and animals with effective antidiarrheal and growth promotion activities ( 28 , 29 ). Lower doses of zinc, especially in organic forms, can reduce diarrhea and promote the growth of young animals ( 10 , 15 , 25 ). In agreement with these findings, the present study found that dietary supplementation with ZnP linearly increased total DMI, ADG, and feed efficiency, thus increasing the final BW of preweaned dairy calves.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an essential nutrient element and is involved in many physiologic functions in the body (7). Dietary zinc supplementation has been found to increase growth performance, promote antioxidant and immune activities, improve the intestinal microflora, and reduce the incidence of diarrhea (8)(9)(10). Although oral administration of large amounts of zinc oxidant (ZnO) was often used to promote growth and reduce diarrhea in young animals (11), unabsorbed zinc secreted in feces may post a threat to the environment.…”
Section: Introductionmentioning
confidence: 99%